Assessment of digital transformation of the SFS Customs of Ternopil region and its impact on the activity of foreign economic entities - I.V. Strutynska (Економіка, управління та адміністрування)
The article examines the basic forms and types of customs control carried out in Ternopil region, evaluates the process of implementation of the WTO agreement on trade facilitation for customs regulation and customs procedures in the region, as well as studies the main aspects of SFS Ternopil Customs. The main aspects of digital transformation of the Customs of the State Fiscal Service (SFS) of Ternopil region are investigated. Based on the analysis of the results of the in-depth survey of 16 respondents, the economic entities engaged in foreign economic activity (FEA), a list of the main positive aspects and issues of SFS Ternopil Customs is formed and the impact of the corresponding changes on the activity of the FEA entities is reflected. The author makes a number of proposals to improve the efficiency of the regional customs authority from the position of the FEA entities. The corresponding study was prepared within the framework of the project «Public Assessment of Regional Customs Authority and Development of Modern Guidelines for Improvement of Customs Control at the Regional Level», implemented by the Public organization «Center for Strategic Development and Reforms» (Ternopil) with the financial support of the European Union.